Performance of QuantiFERON-TB Gold Plus assays in children and adolescents at risk of tuberculosis: a cross-sectional multicentre study. Issue 12 (7th December 2021) - Soler-Garcia, Aleix; Gamell, Anna; Pérez-Porcuna, Tomàs; Soriano-Arandes, Antonio; Santiago, Begoña; Tórtola, Teresa; Ruiz-Serrano, María Jesús; Korta Murua, José Javier; Bustillo-Alonso, Matilde; Garrote-Llanos, María Isabel; Rodríguez-Molino, Paula; Piqueras, Ana Isabel; et al.
Abstract : Introduction: The QuantiFERON- TB Gold Plus (QFT-Plus) assay, which features two antigen-stimulated tubes (TB1 and TB2) instead of a single tube used in previous-generation interferon-gamma release assays (IGRAs), was launched in 2016. Despite this, data regarding the assay's performance in the paediatric setting remain scarce. This study aimed to determine the performance of QFT-Plus in a large cohort of children and adolescents at risk of tuberculosis (TB) in a low-burden setting. Methods: Cross-sectional, multicentre study at healthcare institutions participating in the Spanish Paediatric TB Research Network, including patients <18 years who had a QFT-Plus performed between September 2016 and June 2020. Results: Of 1726 patients (52.8% male, median age: 8.4 years), 260 (15.1%) underwent testing during contact tracing, 288 (16.7%) on clinical/radiological suspicion of tuberculosis disease (TBD), 649 (37.6%) during new-entrant migrant screening and 529 (30.6%) prior to initiation of immunosuppressive treatment. Overall, the sensitivity of QFT-Plus for TBD (n=189) and for latent tuberculosis infection (LTBI, n=195) was 83.6% and 68.2%, respectively. The agreement between QFT-Plus TB1 and TB2 antigen tubes was excellent (98.9%, κ=0.961). Only five (2.5%) patients with TBD had discordance between TB1 and TB2 results (TB1+/TB2−, n=2; TB1−/TB2+, n=3). Indeterminate assay results (n=54, 3.1%) were associated with young age, lymphopenia and elevated C reactive protein concentrations. Conclusions: Our non-comparative study indicates that QFT-Plus does not have greater sensitivity than previous-generation IGRAs in children in both TBD and LTBI. In TBD, the addition of the second antigen tube, TB2, does not enhance the assay's performance substantially.